Transportation Costs and the Great Divergence - Leonid V. Azarnert (Center for Economic Studies and ifo Institute (CESifo), 2014)
This work shows the asymmetric effect of the reduction in transportation costs across different sectors in the process of the Great Divergence. Specifically, the analysis indicates that reductions in transportation costs of industrial goods enhance convergence of the growth rates of trading economies. In contrast, reductions in transportation costs of non-industrial goods contribute to a further divergence across countries.
Keywords: F11; F43; J10; N30; O40; 330; international trade; trade costs; transportation revolution; fertility; economic growth